The concept and practice of Fanconi Anemia: from the clinical bedside to the laboratory bench - Wu, Zhan-He (Translational Pediatrics; Vol 2, No 3 (July 26, 2013): Translational Pediatrics, 2013)
Fanconi Anemia (FA) is characterised with multiple gene mutations, multiple types of genetic abnormalities, multiple organ involvements and multiple types of cancer risks. It is a life threatening disease commonly at 5 years old children. Research on FA is one of the fastest areas in medical research field. The identification of 15 different FA genes and the elucidation of the FA molecular pathways have translated into the understanding of the pathogenic mechanism and practically provided the directions for therapies. Studies on FA rendered invaluable information for the studies on cancers because FA possesses the unique features in many different biological aspects. Studies revealed the genetic linking between FA and cancers that FA genes are in cancers and cancers genes are in FA. As a result, FA is named as a paradigmatic disease for the understanding of cancer and aging. In clinical practice, an early and accurate diagnosis of FA before the stage of bone marrow failure, cancer/leukemia is crucial for the adequate treatment, the prevention of serious medical complications and also for the properly management in the other caring areas including paediatric, hematology, immunology, endocrinology, reproductive/IVF, obstetrics and surgery. However, an early and accurate diagnosis for FA is often difficult because FA is genetically and phenotypically heterogeneous disease. Diagnosis in more or less cases can be delayed until bone marrow failure or cancer/leukemia occurs. As a result that delayed or misdiagnosis even wrong treatment received for patients with FA are not uncommon events clinically in some regions or countries due to the lack of recognition of FA from the clinicians and the limitation in testing resource in laboratory. In this review, the new concept, brief clinical characteristics, research advancing, diagnostic guidelines/differential diagnosis, laboratory testing issues and strategies on FA are discussed.